Being single in parenting: Constructing and reflecting the experiences of international PhD student mothers in pursuing a study by utilizing the collaborative autoethnography method - Trisnawati, Diana; Gunartati,; Utami , Wulan Tri Puji; Prilanita, Yeni Nur; Ratih, Suci Puspita; Putri, Tri Wahyu Oktaviana; Puspitasari, Evi (Journal of International Students, 2026)
This study examined the coping strategies employed by international PhD student mothers (IPSMs) to navigate the complex challenges encountered throughout their PhD journeys. This study utilized the collaborative autoethnography (CAE) method to investigate the experiences of five IPSMs who were engaged in collective reflection. The IPSMs revealed that their journeys were not solely academic endeavors but rather meaningful experiences that fostered resilience and adaptation, enabling them to contribute significantly to ecological system theory (EST). They identified key strategies for balancing their dual roles by constructing and reflecting on their experiences, such as affirming a positive mindset to enhance self-efficacy, connecting with communities and involving children in academic activities. The findings underscore the importance of campus support systems that highlight the role of mentorship, flexible policies and inclusive environments in mitigating the challenges faced.